Motivation determines Facebook viewing strategy: An eye movement analysis. (March 2016) - Scott, Graham G.; Hand, Christopher J.
Abstract: Individuals' Social Networking Site (SNS) profiles are central to online impression formation. Distinct profile elements (e.g., Profile Picture) experimentally manipulated in isolation can alter perception of profile owners, but it is not known which elements are focused on and attributed most importance when profiles are viewed naturally. The current study recorded the eye movement behaviour of 70 participants who viewed experimenter-generated Facebook timelines of male and female targets carefully controlled for content. Participants were instructed to process the targets either as potential friends or as potential employees . Target timelines were delineated into Regions of Interest (RoIs) prior to data collection. We found pronounced effects of target gender, viewer motivation and interactions between these factors on processing. Global processing patterns differed based on whether a 'social' or a 'professional' viewing motivation was used. Both patterns were distinct to the 'F'-shaped patterns observed in previous research. When viewing potential employees viewers focused on the text content of timelines and when viewing potential friends image content was more important. Viewing patterns provide insight into the characteristics and abilities of targets most valued by viewers with distinct motivations. These results can inform future research, and allow new perspectives on previous findings. Highlights: Viewer motivation and profile gender influences processing of social network sites. When viewing potential employees, text content is focused more than image content. When viewing potential friends, image content is focused more than text content. Female profiles viewed as employees were evaluated on physical attractiveness. Male profiles viewed as employees were evaluated on information content.